Variations in relative age effects in individual sports: Skiing, figure skating and gymnastics - Baker, J.; Janning, C.; Wong, H.; Cobley, S.; Schorer, J. (European Journal of Sport Science, 2014)
In many sports, policy-makers and administrators employ annual cohorts to reduce differences between athletes during childhood and youth. Although well-intended, unintended relative age effects (RAEs) usually occur. RAEs refer to the specific selection, participation and attainment disadvantages associated with participants` birthdates relative to an arbitrary `cutoff` date used to group participants within annual age groups. To date, we have little understanding of RAEs in individual sports. In this article, Study 1 considered the presence of RAEs in 1474 ski jumping, 7501 cross-country skiing, 15,565 alpine skiing, 4179 snowboarders and 713 Nordic combined athletes. Chi-square analyses revealed significant RAEs for most of these contexts across sexes. In Study 2, RAEs in the aesthetic sports of figure skating (n=502) and female gymnastics (n=612) were considered. There was no effect for the figure skaters and an atypical effect for the gymnasts. The significant effects across most ski sports coupled with the null effects in figure skating and atypical effect in gymnastics suggest that sport-specific contextual factors are important elements in understanding the mechanisms of RAEs, although further work is necessary to validate these findings.